A model of the impact of land use change on its carbon sequestration capacity - Xu Huang; Wei Lyu; Haiyan Ye; Longshun Su (PLoS ONE, 2025)
Different land-use types have different carbon sequestration capacities, and changes in land-use type directly cause changes in carbon sequestration capacity. To understand the change trend of carbon sequestration capacity, it is necessary to quantify the specific quantity of the impact of land use change on carbon sequestration capacity to indirectly estimate the change in carbon sequestration capacity by monitoring the change in land use type. Based on the analysis of the changing trends of land use type data and ecological carbon sequestration data in the research area, this study establishes an impact model (IM) of land use change on ecological carbon sequestration capacity, quantifying the specific quantity of the impact of land use change on ecological carbon sequestration capacity from two aspects: the impact of land use type transition in and the impact of land use type transition out. Through verification of the accuracy of the model estimation, it is expected that the impact of land use change on carbon sequestration capacity in Sichuan mountainous areas in 2025 and 2030 will be -20754 tons and -30837 tons, respectively, and the total ecological carbon sinks will be 132 and 133 million tons, respectively. Based on the trend analysis of the total carbon sequestration and the IM estimation data, the impact of land use change on ecological carbon sequestration capacity tends to stabilize (the impact will fluctuate around -31156 tons), and the trend of a significant increase in total carbon sequestration is not obvious. The IM quantifies the specific quantity of the influence of land-use type change on carbon sequestration capacity and can dynamically analyze the external factors that cause the change in carbon sequestration capacity, which is of great significance for monitoring the change law of carbon sequestration capacity.